Molecular Docking Sianidin dan Peonidin sebagai Antiinflamasi pada Aterosklerosis Secara In Silico - Saputra, Diajeng Putri Dwinda; Susanti, N. M. P. (Jurnal Farmasi Udayana; Vol. 7, No. 1, Tahun 2018DO - 10.24843/JFU.2018.v07.i01.p04, 2018)
Atherosclerosis is a chronic inflammatory disease that begins with endothelial dysfunction resulting in plaque growth in the inner walls of the arteries. Endothelial dysfunction causes endothelial activates NF-?B resulting in a transcription of proinflammatory gene supporting the growth of atherosclerotic plaque. The purple sweet potato anthocyanin is a compound known to have activity inhibiting the inflammatory process. The major anthocyanins contained in purple sweetpotato are cyanidine and peonidine. The cyanidine and peonidin activity test was performed as antiinflammatory at atherosclerosis based on their interaction on NF-?B protein using molecular docking method in silico. The stages of this research are preparation of protein structure database of NF-?B, protein preparation using Chimera1.10.1 application, preparation and optimization of cyanidin and peonidin 3D structure using HyperChem8 application, and validation of molecular docking and docking method of cyanidin and peonidin on NF-?B protein using application Autodock4.2. The results showed that cyanidine and peonidine had affinity and formed a hydrogen bond with the NF-?B protein. The bond energy between cyanidine and peonidine with the NF-?B protein is -7.92 kcal/mol and -7.86 kcal/mol which together form the hydrogen bond with the LEU472 amino acid on the binding site equal to the native ligand. Cyanidin and peonidine have the potential of activity as antiatherosklerosis because it has an affinity with the NF-?B protein so that it prevents the inflammatory process in the formation of atherosclerotic plaque.